Unusual size dependent strengthening mechanisms of Cu/amorphous CuNb multilayers. (November 2016) - Fan, Z.; Xue, S.; Wang, J.; Yu, K.Y.; Wang, H.; Zhang, X.
Abstract: Nanostructured crystalline/amorphous metallic multilayers have been increasingly studied due to their high strength and potential enhancement of plasticity in amorphous metals. Here we report on mechanical behaviors of Cu/amorphous CuNb multilayers that were prepared by magnetron sputtering with equal individual layer thickness (h) varying from 1 to 200 nm. A medium-range-order amorphous CuNb layer formed between Cu and amorphous CuNb layers. This intermediate layer facilitates transmission of plasticity from Cu to amorphous layers by preventing the smear of dislocation core on the interface. The maximum hardness of Cu/amorphous CuNb multilayers is achieved when h ≤ 50 nm, and is much lower than the hardness of single-layer amorphous CuNb films. Molecular dynamics simulations show that, comparing with single-layer amorphous CuNb, the pile-up of dislocations in Cu layers lowers the stress for the activation of shear transformation zones in amorphous CuNb layers in multilayers. Graphical abstract: Image 1